Pediatric multifocal histiocytic sarcoma- a fatal diagnosis not to miss! - Darilin Shangpliang; Pakesh Baishya; Vandana Raphael; Biswajit Dey; Vikas Kantilal Jagtap (University of São Paulo, 2021)
Histiocytic sarcoma (HS) is a rare hematolymphoid malignant neoplasm with an aggressive clinical course. It can arise de novo or from low-grade B-cell lymphoma. We describe the case of a 16-year-old boy referred to our hospital with generalized lymphadenopathy, weight loss, and decreased appetite for one month. The patient died undiagnosed on the 7th day of hospitalization. Lymph node and bone marrow biopsies were performed one day before the patient died. The lymph node biopsy revealed an architectural effacement with a diffuse proliferation of large pleomorphic neoplastic cells containing large, multilobulated nuclei, coarse vesicular chromatin, prominent nucleoli, and a moderate amount of eosinophilic cytoplasm. The bone marrow aspiration smears and biopsy also showed evidence of infiltration by these above-mentioned cells. Based on the morphology, along with the exclusion of many differential diagnoses by an extensive panel of immunohistochemical markers, a diagnosis of HS was made. This case report aims at evaluating all the clinical and immunophenotypic features of a case of HS with multifocal presentation and an aggressive clinical course in order to give a correct and definite diagnosis at the proper time.